Analyzing raw water quality of drinking water of Pelayaran River: Tribute to Brantas River - Oktavia, L.; Karnaningroem, N.; Wirjodirdjo, B.; Titah, H. S. (International Journal Labs, 2024)
Raw water quality for drinking water is a strategic issue requiring attention and environmental dynamics. River quality changes are crucial for sustainability and monitoring suitability. Kali Pelayaran, a tributary of the Brantas River, is a key source for drinking water in Sidoarjo Regency. The aim of the research is to analyze the water quality status of the Kali Pelayaran river as a basis for mitigating the sustainability of raw drinking water in Sidoarjo Regency. The length of the segment analyzed starts from the upstream branch of the Brantas River which enters the Pelayaran River to the intake of the Tawangsari WTP, a distance of 21 kilometers. The research method that will be implemented is: analyzing the existing condition of the water quality of the Kali Pelayaran river which is divided into 8 segments by measuring the quality status of the river using the Pollutant Index (IP). Next, use the K-means method to create clustering based on the measured level of quality status. The water and sediment quality parameters analyzed were pH, temperature, DO (Dissolved oxygen), BOD (Biological oxygen demand), COD (Chemical oxygen demand), TDS (Total dissolved solids), and TSS (Total suspended solid). Research conclusions was formulated in an integrated manner regarding the description of current conditions and predictions for the future, presented in the form of tables, graphs, and maps.